DEVELOPMENT OF THE HOTS-BASED “PROK-PROK” GAME APPLICAION TO IMPROVE CRITICAL THINKING SKILLS AND SOCIAL STUDIES LEARNING ACHIEVEMENT OF FIFTH-GRADE STUDENTS AT SDN SUKOLILO 01 - Ellenna Ayu Maywulandari; Parji; Sudarmiani (RADJA PUBLIKA, 2026)
The research aims to develop a HOTS-based “Prok-Prok” game application and test its feasibility, effectiveness, and practicality in improving critical thinking skills and social studies learning achievement results of class V SDN Sukolilo 01. The research uses the Research and development method with the ADDIE development model including the stages of analysis, design, development, implementation, and evaluation. Data collection techniques use questionnaires and tests (Pre-test and Post-test), while data analysis techniques use descriptive analysis and the Wilcoxon test. The results of the research are as follows: (1) a HOTS-based “Prok-Prok” game application learning media has been developed which contains the material of the Proclamation of Indonesian Independence to improve critical thinking skills and social studies learning achievement results of class V SDN SUKOLILO 0; (2) the developed learning media is declared valid with an average percentage score of 81.81% from the media aspect while 86.67% from the material expert; (3) the practicality aspect, the media obtained an average percentage score of 85%, which shows that the media is practical to use in the learning process; (4) effectiveness aspect, the results of the Wilcoxon test show the results of the Wicoxon test with an Asymp.Sig. (2-tailed) value of 0.001, which means that Ho is rejected and Ha is accepted. It can be concluded that the HOTS-based “Prok-Prok” game learning media is able to improve critical thinking skills and the learning achievement results of class V Social Studies at SDN Sukolilo 01